Dietary Dietary Habit of Pregnant Women on The Incidence of Anemia - Fitriana Ikhtiarinawati Fajrin; Khusul Nikmah; Husnul Muthoharoh (MBUnivPress, 2023)
A good dietary habit during pregnancy can meet the body's needs during pregnancy and can support the health of the baby. Dietary habit is the composition of the type and amount of food consumed by a person at a certain time. This study aims to determine the relationship between the dietary habit of pregnant women and the incidence of anemia. This research is an analytic survey research and uses a cross sectional research design. The time of the research was carried out on March 10, 2023. The population in this study were all 26 pregnant women who were undergoing pregnancy checks. The sampling technique used is total sampling. The univariate data analysis technique used the frequency distribution while the bivariate used the Chi Square test. The conclusion in this study is that there is a significant relationship between the dietary habit of pregnant women and the incidence of anemia with p = 0.003 (<0.05). Pregnant women who do not have a good dietary habit have 4 times the risk of experiencing anemia compared to pregnant women who have a good diet with an OR (Odd Ratio) value of 4.031.